The role of conflict management strategies in achieving organizational justice - an analytical study at the University of Karbala - Ali Ahmed Faris ,; Zainab Makki Albanaa ,; Jinan Mahdi Aldahhan, (Iraqi Journal for Administrative Sciences, 2024)
The study aims to determine the role of choosing the right strategy for the conflict in order to achieve organizational justice. The study sample consisted of (64) as director of administrative departments and in some faculties of the University of Karbala. The study uses questionnaire to see the effect of the use of conflict management strategies through its dimensions (competition, avoidance, compromise, cooperation, compromise) in the reduction of conflicts to achieving organizational justice (distributive, interactive, procedural) between individuals. The study conclusion is affecting strategies the achievement of distributive and procedural justice is the comprising strategy in the sense achieve a higher degree of participation in benefits while a strategy of cooperation the greatest impact in achieving interactive justice in the sense that teamwork in resolving conflicts over cases of interactive justice that rely the fairness of the behavior of decision makers. Where the study recommended increasing concern for justice distributional it the most effect on the lives of individuals and have the big morale influence as directly related to the level of income and social well-being and because distributive justice realize by individuals as a standard treatment organization for them then they should manage the conflict to achieve the highest standards of justice and the distribution of output organized fair to everyone.